Motion of Ship-Shaped Floating Liquefied Natural Gas - Koto, Jaswar (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2014)
Floating Liquefied Natural Gas (LNG) recently are new in the offshore platform and operation, since it is new so it is important to analyzed the stability and seakeeping of this vessel. This project are conducting stability assessment and seakeeping of Floating Liquefied Natural Gas (LNG) with initially it has to design the hull by referring the basic dimension of FPSO KIKEH that located at the 120 km northwest of Labuan Island which is the environmental location of this project. Hence this project are using Maxsurf for designing the hull, Hydromax to do stability assessment and Seakeeper for seakeeping analysis which is to generate wave spectrum and Response Amplitude Operator and hence to analyzed the motion characteristic of this vessel behavior in the research location.